• Brainly User
Here's what you got, x²+y²+z²-xy-yz-zx=0. Multiply this equation with 2. You get this, 2x²+2y²+2z²-2xy-2yz-2zx=0. Rearrange the terms in this manner, (x²-2xy+y²) + (y²-2yz+z²) + (z²-2zx+x²)=0. You have, (x-y)²+(y-z)²+(z-x)²=0. Here's a little brain work you need to do. You might be knowing that the square of a real number is either zero or positive. Now, see that the terms on the L.H.S. are all squares of real numbers ( if you think of x, y, z to be real numbers instead of complex, which you forgot to mention ) and the R.H.S. is 0. Hence, each term has to be 0, if this were not so the L.H.S. would be positive. So you have, x-y=0 and y-z=0 and z-x=0 giving you x=y=z.
If x, y, z, aren't real, this result wouldn't apply.

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
X² + y² + z² -xy - xz - yz = 0
multiplying 2 on both sides

2x² + 2y² + 2z² - 2xy - 2xz - 2yz = 0
x² + y² - 2xy+ x² + z² - 2xz + z² + y² - 2yz  = 0
(x - y)² + (x - z)² + (y - z)² = 0

so the  value are in square so they can't be negative so they must be indivudually zero to satisfy the equation 

so x - y = 0 ⇒ x = y 
    x - z = 0 ⇒ x = z 
    y - z = 0 ⇒ y = z 

so hence x = y = z proved